2008
DOI: 10.1002/jso.21074
|View full text |Cite
|
Sign up to set email alerts
|

Is gastrectomy mandatory for all residual or recurrent gastric cancer following endoscopic resection? a large‐scale Korean multi‐center study

Abstract: Background and Objectives: To clarify optimal treatment guidelines for residual or local recurrence after endoscopic resection (ER). Methods: Eighty-six patients underwent gastrectomy due to incomplete ER and local recurrence after ER. The pathological findings of ER and gastrectomy specimens were analyzed. Results: The cause of gastrectomy was categorized into five groups; submucosal (sm) invasion without margin involvement, positive margin, margin not evaluable, high risk of lymph node metastasis and local r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
30
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 28 publications
(30 reference statements)
3
30
0
Order By: Relevance
“…these criteria were obtained from studies that investigated pathological findings of gastrectomy specimens with LN dissection from a mostly Japanese dataset (7,10,11). to validate these criteria and the adequacy of er for egc, several studies have reported the clinical outcome of egcs treated with er (5,(12)(13)(14)(15). oda et al reported the clinical and surgical outcomes of 144 egcs, which were treated with er and underwent further surgical treatment due to the risk of ln metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…these criteria were obtained from studies that investigated pathological findings of gastrectomy specimens with LN dissection from a mostly Japanese dataset (7,10,11). to validate these criteria and the adequacy of er for egc, several studies have reported the clinical outcome of egcs treated with er (5,(12)(13)(14)(15). oda et al reported the clinical and surgical outcomes of 144 egcs, which were treated with er and underwent further surgical treatment due to the risk of ln metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, gastrectomy with lymph node dissection should be performed for patients with submucosal invasion with or without margin involvement after noncurative ESD [24]. However, it remains unclear whether a modified resection technique such as PG or PPG with D1 or D1?…”
Section: Discussionmentioning
confidence: 99%
“…Even after the complete removal of the primary lesion by ESD, many patients require radical gastrectomy with LN dissection due to the risk of LN metastases [21,22]. However, pathological results after radical gastrectomy with LN dissection revealed that most of these patients did not have LN metastases [22].…”
Section: Discussionmentioning
confidence: 99%